FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS RESPONSE COEFFICIENT (ERC) PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2012 (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
This study tries to re-examine the factors that affect Earnings Response Coefficient(ERC) companies listed on the Stock Exchange in 2012. The independent variablesconsist of earnings persistence, growth companies, the risk of the company, thecompanys capital structure and firm size. Samples were obtained as many as 85companies through purposive sampling method with criteria. Hypothesis testingusing multiple regression analysis with significance level Î± = 5%. From the results ofdata processing with multiple regression obtained variable results the companysgrowth and the companys capital structure significantly influence the ERC. Whilevariable persistence of earnings, the companys risk, and the size of the companydoes not have a significant effect.Keywords: ERC, the persistence of earnings, growth, enterprise risk, capitalstructure, size company